Financial Literacy in Moderating Lifestyle and Money Attitudes to Adolescent Financial Management Behavior - Ayu Kusumaningsih; Muhammad Ulin Nuha (Universal Business and Management Review, 2026)
This study aims to determine the role of financial literacy in moderating the relationship between lifestyles, money attitudes, and financial management behaviors of adolescents. The research method used is an empirical study by taking a sample of MA Miftahul Huda students as a research population. Data was collected through questionnaires that assessed financial literacy levels, lifestyles, money attitudes, and financial management behaviors. Data analysis was carried out using multiple regression techniques to determine the influence of these variables. The results of the study show that financial literacy plays an important role in moderating the relationship between lifestyle and money attitudes towards adolescents' financial management behavior. In particular, financial literacy increases adolescents' understanding of the importance of personal financial management, thereby encouraging them to adopt more thoughtful behaviors in managing money and managing lifestyles according to their financial needs.